Impact of Low‐Latitude Ionospheric Effects on Precise Position Determination. Issue 4 (28th March 2022) - Biswas, T.; Banerjee, P.; Paul, A.
Abstract: Precise Point Positioning (PPP) techniques serve as a very important tool, to provide high precision position information, using data from a grid of networked receivers. However, satellite signals are frequently perturbed by inhomogeneities present in the medium of propagation, introducing errors in the measured position, the dominant contribution of which could be attributed to the ionosphere. Low‐latitude stations, like Calcutta (22.58°N, 88.38°E geographic; magnetic dip 34.54°), being situated near the northern crest of Equatorial Ionization Anomaly (EIA), experience some of the worst cases of ionospheric effects on position determination. However, such effects are usually minimal during early morning hours (typically 03–05 local time [LT]). In this study, PPP of the station Calcutta has been obtained under different solar activity conditions to assess and validate the applicability of sub‐centimeter level position accuracy. The PPP values have also been compared with early morning stand‐alone dual‐frequency GPS receiver‐derived position to assess and validate the diurnal ionospheric quiet time. Efforts have also been made to observe the effects of EIA on PPP solution. Data are recorded during a high (March 2014) and low (March 2019) solar activity period. Results of this study reveal agreement with the centimeter‐level accuracy of PPP; however, effect of solar activity is prominent when inspected in millimeter order. Additionally, the diurnal ionospheric quiet time is observed to lie within 04–06 and 02–04 LT for a high and a low solar activity period, respectively. Irrespective of the solar activity conditions, receiver noise contribution in position deviation is measured to be within 150 cm. Key Points: Applicability of sub‐centimeter level position accuracy by Precise Point Position (PPP) at a low‐latitude station Study of stand‐alone dual‐frequency Global Positioning System (GPS) receiver position during diurnal ionospheric quiet time Comparison of GPS receiver‐derived position with PPP for characterization of system errors